Characterization of the staphylococcal beta-lactamase transposon Tn552. - Rowland, S J (1989)
The staphylococcal beta-lactamase transposon Tn552 is a member of a novel group of transposable elements. The organization of genes in Tn552 resembles that of members of the Tn21 sub-group of Tn3 family transposons, which transpose replicatively by cointegrate formation and resolution. Thus, a possible resolution site ('resL') and a resolvase gene (tnpR or 'binL') have been identified. However, consistent with the fact that Tn552 generates 6 bp (rather than 5 bp) flanking direct repeats of target DNA, neither the putative transposase protein, nor the terminal inverted repeats of Tn552 are homologous to those of Tn3 elements. Tn552, like phage Mu and retroelements, is defined by the terminal dinucleotides 5' TG .. CA 3'. A naturally occurring staphylococcal plasmid, pI9789, contains a Tn552-derived resolution system ('resR-binR') that acts as a 'hotspot' for Tn552 transposition; insertion creates a segment of DNA flanked by inversely repeated resolution sites, one (resR) on pI9789 and the other (resL) on Tn552. The putative Tn552 resolvase, the most closely related of known resolvases to the homologous DNA invertases, initially was identified as a DNA invertase ('Bin') as a result of its ability to mediate efficient inversion of this segment in vivo.